Alpha-, Delta- and PP-cells: Are They the Architectural Cornerstones of Islet Structure and Co-ordination?. (August 2015) - Brereton, Melissa F.; Vergari, Elisa; Zhang, Quan; Clark, Anne
Islet non-β-cells, the α- δ- and pancreatic polypeptide cells (PP-cells), are important components of islet architecture and intercellular communication. In α-cells, glucagon is found in electron-dense granules; granule exocytosis is calcium-dependent via P/Q-type Ca 2+ -channels, which may be clustered at designated cell membrane sites. Somatostatin-containing δ-cells are neuron-like, creating a network for intra-islet communication. Somatostatin 1-28 and 1-14 have a short bioactive half-life, suggesting inhibitory action via paracrine signaling. PP-cells are the most infrequent islet cell type. The embryologically separate ventral pancreas anlage contains PP-rich islets that are morphologically diffuse and α-cell deficient. Tissue samples taken from the head region are unlikely to be representative of the whole pancreas. PP has anorexic effects on gastro-intestinal function and alters insulin and glucagon secretion. Islet architecture is disrupted in rodent diabetic models, diabetic primates and human Type 1 and Type 2 diabetes, with an increased α-cell population and relocation of non-β-cells to central areas of the islet. In diabetes, the transdifferentiation of non-β-cells, with changes in hormone content, suggests plasticity of islet cells but cellular function may be compromised. Understanding how diabetes-related disordered islet structure influences intra-islet cellular communication could clarify how non-β-cells contribute to the control of islet function.